Interpersonal guilt and the working alliance in psychotherapy: The moderating role of childhood experience. (17th September 2022) - Aafjes‐van Doorn, Katie; Luo, Xiaochen; Kealy, David; McCollum, James; Silberschatz, George
Abstract: Interpersonal guilt often encompasses pathogenic beliefs that imply omnipotent responsibility for others and concerns about abandoning, humiliating or threatening others. This study sought to examine how interpersonal guilt may influence patients' and therapists' ratings of early working alliance and the potential moderating effect of perceived adverse parenting in childhood. Ninety‐five patients and their 19 therapists in an outpatient psychotherapy clinic rated their early working alliance after the first and the fifth session in treatment. We conducted separate moderation analyses for patient and therapist‐reported working alliance and controlled for psychological distress at baseline. Results suggest that perceived adverse parenting in childhood significantly moderated the effect of interpersonal guilt on the working alliance in such a way that for patients reporting very low levels of perceived adverse experiences, the interpersonal guilt beliefs had a positive effect on working alliance, whereas for those with very high levels of perceived adverse experiences, interpersonal guilt had a negative effect on working alliance. This same pattern of moderation was found for patient‐ and therapist‐reported working alliance at session 1 and therapist‐reported working alliance at session 5. Thus, although the effect of interpersonal guilt on the working alliance depends somewhat on the perspective of the working alliance rating (patient or therapist), it mainly depends on developmental experiences of the patient.